Dark Septate Endophytes Improve the Growth and the Tolerance of Medicago sativa and Ammopiptanthus mongolicus Under Cadmium Stress - Hou, Lifeng; Yu, Jie; Zhao, Lili; He, Xueli (Frontiers in Microbiology, 2020)
ABSTRACT Although the ecological function of dark septate endophytes (DSEs) is well studied, little is known about the host plant responses to DSEs obtained from other plants, especially under conditions of heavy metal stress. This study aimed to investigate how DSEs from heavy metal habitat affect non-host plants in cadmium (Cd) stress soils, which then provide basis for the application of DSEs in the cultivation of different plants and soil remediation strategies for polluted ecosystems. We isolated and identified two species of DSE (Acrocalymma vagum and Scytalidium lignicola) inhabiting the roots of Ilex chinensis (host plant) grown in metal-polluted habitats. Then, the Cd-stress tolerance of the DSEs was tested using a pure Cd concentration adjusted culture. Subsequently, we examined the performance of non-host plants (Medicago sativa and Ammopiptanthus mongolicus) inoculated with DSEs under Cd stress in a growth chamber. The results indicated that two DSEs could grow under Cd stress in vitro, even when not exhibiting high levels of tolerance to Cd. The superoxide dismutase (SOD), malondialdehyde (MDA), glutathione (GSH), soluble protein, and melanin of DSE fungi reached maximal levels at concentrations of 30–60 mg Cd/L, indicating the important preventive strategies adopted by DSE fungi in environments contaminated by Cd. Despite a decreased biomass of DSE hyphae with enhanced Cd concentrations, the accumulation of Cd in DSE hyphae tended to shown an increasing trend. Both DSEs were effective colonizers of the non-host plants. A. vagum and S. lignicola inoculation significantly promoted the biomass and root architecture of the two non-host plants under Cd stress. A. vagum inoculation increased the total nitrogen of A. mongolicus, whereas inoculation with S. lignicola significantly increased the organic carbon of M. sativa. In particular, DSEs inoculation significantly improved the accumulation of Cd in plant tissues under Cd stress, demonstrating a potential application in the bio-remediation of heavy metal pollution areas. Our findings suggest that DSE inoculation improved the root growth and nutrient absorption of non-host plants, altered the soil Cd concentration, and facilitated plant growth and survival under Cd stress. These results contribute to better understanding DSE-plant interactions in habitats contaminated by heavy metals.